Analisis Pengaturan Ambang Batas Pencalonan Presiden Menurut Putusan Mahkamah Konstitusi Tahun 2022-2023 - Soeoed, Mochamad Rizky (UI Scholars Hub, 2023)
The constitutional amendments that took place from 1999 to 2022 emphasized that Indonesia adheres to a presidential system of government. One way that is often discussed to increase the effectiveness of the presidential government system is to hold elections simultaneously by implementing the presidential nomination threshold which is now regulated in article 222 of Law Number 7 of 2017 concerning Elections which provides conditions for political parties to obtain a minimum of 20 percent of DPR seats. or 25 percent of valid national votes to be able to nominate candidates for President and Vice President. In practice, this provision always invites controversy and has been repeatedly tested at the Constitutional Court. This article will explain in detail how the threshold for presidential candidacy is set in Indonesia. Then, this article will also analyze the threshold for presidential candidacy according to the decision of the constitutional court in 2022-2023. This article was prepared using doctrinal research methods. The research results show that the threshold norms for presidential candidacy are not regulated in the 1945 Constitution of the Republic of Indonesia, the constitution only regulates the victory threshold as stated in article 6 paragraph (3). The threshold norms for presidential candidacy are regulated in detail in laws that regulate the technical implementation of general elections, such as Law No. 23 of 2003, Law No. 42 of 2008, and Law No. 7 of 2017. The Constitutional Court in its decisions always emphasized that the threshold norm for presidential candidacy is an open legal policy and does not conflict with the 1945 Constitution of the Republic of Indonesia. The Constitutional Court considered that the threshold norm for presidential candidacy had a positive impact on a strong presidential government system.